Posture in Voice Training “Freeing Body and Voice” - Kar, Tuğçem (Current Studies in Social Sciences VI, 2023)
The Ideal Voice Training Method can be possible with a sincere collaboration that allows the student to use his / her talent in the most natural way, values ​​the personality of the student, the student can easily surrender himself to the voice trainer and mutual trust is built. The student should know the anatomical structure of the human body, how its functions work and have the knowledge about how to avoid all physical and psychological factors that may prevent this. It is a singer's instrument body. Although the first thing that comes to mind when it comes to vocal training is our diaphragm muscle and throat, vocal training is directly related to the anatomical structure and physiology of our entire body. In this sense, the vocal training process requires the student to use their voice in a healthy and sustainable way; It should also provide gains such as natural breathing and phonation breathing, voice hygiene principles, the discovery of the zero point of the body and mind, and natural posture. Not having a correct posture prevents the vocal cords from functioning optimally while singing. In order for vocal training to be successful, our body must not have unnecessary contractions and our muscles must move in full flexibility. The emotional mood of the singing person should also be free from tension and negativity. For the singer, rigid information about posture can cause the singer to be more nervous. Thus, the flexibility expected of the singer cannot be realized. However, while the singer performs his role on the stage, he will enter from position to position. During singing, it is very important that our respiratory organs and vocal organs are not contracted and not exposed to any tension. Often voice trainers for correct posture "Think of it as a rope above your head is pulling you up." they use the expression. This way, the space between the spine stretches and the body is ready to explore its center. When we sleep, that is, when our consciousness is disabled, all the muscles in our body are expressed as - at the zero point. Again, while sleeping, our respiratory muscles, the diaphragm, abdomen and inter-rib muscles, can work much more flexibly. Since it is a resting breathing, we perform larger and equal inspiration and expiration. Sometimes, when you give verbal advice about breathing well or posture to the singer during the lesson, the person can bore himself more because the control mechanism is activated. The words of the educator can be perceived as direct and create a reverse result. This situation both the breath to be shorter causes and tense and the posture to be upright and impulsive, away from the natural. At such times, resorting to motion will be a savior. The focus of the student should be removed from breathing and posture, and the selectivity of the perception at that moment should be eliminated. It would be best to follow a kinesthetic approach by imagining a moment when the body is comfortable. This approach can even be an easy exercise, such as putting either object in the student's hand and walking with his arms waving. Thus, the student will relax with the movement he / she makes at that moment, release his shoulders, his body will stretch, the larynx will not be squeezed and physical learning will be activated. In the next action, this moment of comfort will recall and increase bodily awareness. With the correct invocation of the movement each time, motor learning will take place, so knowledge and awareness will begin to be permanent. The stance that makes the singer feel comfortable, that he can use the voice possibilities widely and which is also aesthetic should be targeted. Singers often tend to hold their heads up in high-pitched voices, raise their fingertips and pull their chin down in low-pitched voices. However, when they stretch their heads up, the larynx regresses, and when they pull their jaws down, the larynx is compressed. The most important point in singers' postures is that the movements of the head and neck region are coordinated. In tense situations, the opposite movements can be relaxing. For example, lowering their hands or stretching down on their knees while making high-pitched sounds, raising their hands up while falling down to low sounds, or drawing eight with their hands will prevent unwanted neck movement as imagination. In this part of our book, which includes target behaviors in vocal training, the researcher has examined posture in vocal training, starting with the formation of respiration and phonation, the relationship between the spine and posture. And the researcher has also touched on six balance points ( AO Joint, the thorax in relation to the lumbar spine, the hip joint, the knee joint, the ankle joint ( including arches of the feet and foot tripods ) and the arm structure ) in voice training suggested by Melissa Malde , MaryJean Allen, and Kurt-Alexander Zeller. The present study has explained how posture analysis is done with the “ symmetrigraph ” or “ posture analysis v.20” and the necessity of physical awareness for correct posture and pioneers in body awareness methods. The importance of freeing the body and freeing the voice as an attainment of correct posture is emphasized. In addition, the use of analogy, imagination and metaphors in freeing the voice and body is mentioned.